A New Kind of Youth : Historically Black High Schools and Southern Student Activism, 1920-1975 - Hale, Jon N. (Book collections on Project MUSE., 2022)
"The story of activist youth in America is usually framed around the Vietnam War, the counterculture, and college campuses, focusing primarily on college students in the 1960s and 1970s. But a remarkably effective tradition of Black high school student activism in the civil rights era has gone understudied. A New Kind of Youth brings high school activism into greater focus, illustrating how Black youth supported liberatory social and political movements and inspired their elders across the South"--